Pengaruh Sistem Pelaporan, Kompetensi Perangkat Desa, Kepemimpinan Kepala Desa, Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa di Kecamatan Banjarangkan, Kabupaten Klungkung - I Nyoman Jagra Sujatnika; Ni Luh Gede Erni Sulindawati (Universitas Pendidikan Ganesha, 2022)
Research aims to understand the influence of reporting system, the competence of village officials, the leadership of the village head, and public participation, to successful accountability of village fundsManagement. The research is quantitative research using types of data on obtained from the questionnaire and primary is measured using likert scales.The population in this study are village officials and village institutions in all villages in Banjarangkan Subdistrict, Klungkung Regency. The sample collectiontechnique use non-probability sampling that is purposive sampling.The criteria of the samplein this study isthevillage apparatus consisting of; Village head, village secretary, head of financial affairs, head of planning affairs, and village head; village institutions including; the chairman of the LPM, the chairman of the BPD, and the chairman of the PKK; and has a minimum service period of 1 year.Data analysis techniques in this study using multiple linear regression analysis with SPSS version 24. The results of the research indicated that the variable reporting system variable (X1) has a positive and significant effect on the accountability of village funds management, the variable competency of the village apparatus (X2) has a positive and significant effect on the accountability of village funds management, the leadership variable of the village head (X3) has an effect on positive and significant effect on the accountability of village funds management, and public participation variable (X4) has a positive and significant effect on the accountability of village funds management.